1993
DOI: 10.7164/antibiotics.46.1666
|View full text |Cite
|
Sign up to set email alerts
|

A new antibiotic, cypemycin. Taxonomy, fermentation, isolation and biological characteristics.

Abstract: A newpeptide antibiotic, cypemycin, with a molecular weight of 2,097 (M +H), was isolated from the culture broth of Streptomyces sp. OH-4156.The antibiotic possesses cytocidal activity against P388 leukemia cells in vitro at a concentration of 1.3 //g/ml (IC50 values), and the antibiotic showed antimicrobial activities against Micrococcus luteus (MIC, 0.2 /jg/ml).In the course of a screening program for novel antibiotics showing cytocidal activity, cypemycin was isolated from the culture broth of Streptomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 8 publications
2
47
0
Order By: Relevance
“…It was speculated that the greater susceptibility to pore formation of micrococci than that of lactobacilli could reflect, in part, their relatively thinner phospholipid bilayer. The lack of antimicrobial activity observed for grisemycin and the very narrow spectrum reported for cypemycin (11) suggest that these two compounds might serve different roles in the biology of their producing Streptomyces organisms, for example, as signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was speculated that the greater susceptibility to pore formation of micrococci than that of lactobacilli could reflect, in part, their relatively thinner phospholipid bilayer. The lack of antimicrobial activity observed for grisemycin and the very narrow spectrum reported for cypemycin (11) suggest that these two compounds might serve different roles in the biology of their producing Streptomyces organisms, for example, as signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting S. griseus ⌬grmA::[oriT-aac(3)IV] mutant strain was designated M1458. For bioassays, strains were grown for 3 days in cypemycin production medium (11), and culture supernatants were separated from the mycelium by centrifugation and extracted with CHCl 3 . The solvent was evaporated and the residual pellet dissolved in 5% formic acid for matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) analysis or in methanol (MeOH) for use in an M. luteus paper disc bioassay (3).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we identified the cypemycin biosynthetic gene cluster of Streptomyces sp. OH-4156 (7) and show that these previously described modifications are introduced by unusual enzymes or by an unusual modification pathway. Six distinct posttranslational modifications participate in cypemycin biosynthesis, altering 9 of the 22 amino acids found in the mature peptide.…”
mentioning
confidence: 99%
“…Actinobacterial bacteriocins inhibit the growth of species related to the producer, such as michiganin A [13], although many of them possess a broad spectrum of inhibitory activity that includes non-related bacteria (microbisporicin), protozoans (thiostrepton), yeasts and fungi (cinnamycin) and viruses (labyrinthopeptin A1 and duramycin) [14][15][16][17][18]. In addition to antimicrobial activity, some actinobacterial bacteriocins and their semisynthetic derivatives also exhibit anti-inflammatory [19][20][21], anti-allergic [20], antitumour [22][23][24] and antinociceptive activities [25,26], and may also act in blood pressure regulation [19,27]. Some of these peptides have already found clinical applications, such as thiostrepton, a thiopeptide used in dermatologic ointment for veterinary use [28], and others are in stages of pre-clinical and clinical trials, such as NAI-107, NAI-112 [29] and lancovutide/duramycin (https://clinicaltrials.gov/ct2/show/study/ NCT00671736?term=Lancovutide&rank=1; accessed September 17,2016), which reinforces the great potential of practical application of bacteriocins produced by Actinobacteria.…”
Section: Bacteriocins Produced By Actinobacteriamentioning
confidence: 99%